Epidemiology of lower extremities fractures in the population in Vinnitsa region - Povoroznyuk, Vladyslav; Grygorieva, Nataliia; Korzh, Mykola; Strafun, Sergey; Vlasenko, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Lower extremities fractures are ⅓ to ½ of all fractures, that can increase morbidity and mortality. Nowadays there are studies devoted to the age and gender peculiarities of femur fractures in Ukraine, but data of other fractures location is restricted. Objective: to study the frequency and structure of lower extremities fractures depending on the age, sex, location in the population in Vinnitsa region during 2011–2012. Methods: the study was conducted as multicentral epidemiological study RSOF (Registry System of Osteoporotic Fractures). Population of Vinnitsa region was analyzed according to Ukrainian State Committee. We assessed the frequency of lower extremity fractures, its location depending on the age and gender. Results: the frequency of lower extremities fractures is 446,2 per 100 000 in male and 347,45 in female, it increases in patients older than 50 years old (493,1 and 540,1 respectively). Femur fractures prevail in women: 103,0 per 100 000 of population in men and 132,0 in women, after 50 years — 172,1 и 252,4 respectively. Such indexes are connected with the increasing of proximal femur fractures— 158,5 and 228,7 per 100 000 of population. We observed tibia shaft fractures in men more often (226,4 and 162,2 in women) foot fractures (107,2, in women — 43,6 per 100 000). Conclusion: the frequency of lower extremities fractures in population of Vinnitsa region has the age and gender depended peculiarities, which must to be taken into consideration during planning of prophylaxis measures.